High-intensity endurance capacity assessment as a tool for talent identification in elite youth female soccer. Issue 11 (17th June 2020) - Datson, Naomi; Weston, Matthew; Drust, Barry; Gregson, Warren; Lolli, Lorenzo
ABSTRACT: Talent identification and development programmes have received broad attention in the last decades, yet evidence regarding the predictive utility of physical performance in female soccer players is limited. Using a retrospective design, we appraised the predictive value of performance-related measures in a sample of 228 youth female soccer players previously involved in residential Elite Performance Camps (age range: 12.7–15.3 years). With 10-m sprinting, 30-m sprinting, counter-movement jump height, and Yo-Yo Intermittent Recovery Test Level 1 (IR1) distance as primary predictor variables, the Akaike Information Criterion (AIC) assessed the relative quality of four penalised logistic regression models for determining future competitive international squads U17–U20 level selection. The model including Yo-Yo IR1 was the best for predicting career outcome. Predicted probabilities of future selection to the international squad increased with higher Yo-Yo IR1 distances, from 4.5% (95% confidence interval, 0.8 to 8.2%) for a distance lower than 440 m to 64.7% (95% confidence interval, 47.3 to 82.1%) for a score of 2040 m. The present study highlights the predictive utility of high-intensity endurance capacity for informing career progression in elite youth female soccer and provides reference values for staff involved in the talent development of elite youth female soccer players.